1987
DOI: 10.1002/jso.2930350412
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term prophylaxis with cefuroxime in colorectal surgery for cancer

Abstract: A controlled study of short-term prophylaxis with cefuroxime was performed on a group of 52 patients with colorectal neoplasms who underwent elective surgery. The patients were divided into two groups, A and B. Group A received the antibiotic immediately before surgery, intraincisionally and immediately after the end of operation; group B was treated only postoperatively. Each patient received a total of 5,250 mg of cefuroxime. Wound sepsis was demonstrated in 11.5% of cases of group A and 23.0% of group B (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…27,28 In elective colon resection for cancer, the intravenous antibiotics need not be continued longer than 24 hours postoperatively. 29 Although there are several studies proposing the use of a single preoperative dose of antibiotics, [30][31][32][33][34] most of these suffer from a lack of statistical power because of small study size. There is one large, prospective, randomized trial that has shown that a single preoperative dose of cefotaxime and metronidazole is as effective as three doses.…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%
“…27,28 In elective colon resection for cancer, the intravenous antibiotics need not be continued longer than 24 hours postoperatively. 29 Although there are several studies proposing the use of a single preoperative dose of antibiotics, [30][31][32][33][34] most of these suffer from a lack of statistical power because of small study size. There is one large, prospective, randomized trial that has shown that a single preoperative dose of cefotaxime and metronidazole is as effective as three doses.…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%